Can functional buoyancy and floating angle predict success in learning beginning swimming skills among young men? - Stallman, R. K.; Stallman, R. K.; Horneman, E. L.; Laakso, B. W. H. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION A common belief is that those who float better or float closer to the horizontal, learn to swim more easily. It is supposed that they have some kind of `head start`. While this sounds quite logical, little if any data is available to confirm it. If such an advantage does exist, it should be possible to quantify it. A head start of any kind is of course, always welcome.